How to draw dinosaurs - Smith, Frank Charles, 1937- (New York : Scholastic, 1985)
Demonstrates in step-by-step format how to draw dinosaurs.
3.0
3-6
Keywords: Drawing -- Technique -- Juvenile literature; Dinosaurs in art -- Juvenile literature; Drawing -- Technique; Animal painting and illustration; Dinosaurs in art; Drawing -- Technique; Animal painting and illustration; Dinosaurs in art